2007
DOI: 10.1093/eurheartj/ehn123
|View full text |Cite
|
Sign up to set email alerts
|

Impact of resting heart rate on outcomes in hypertensive patients with coronary artery disease: findings from the INternational VErapamil-SR/trandolapril STudy (INVEST)

Abstract: Among CAD patients with hypertension, RHR predicts adverse outcomes, and on-treatment RHR is more predictive than baseline RHR. A Ve strategy is less effective than an At strategy for lowering RHR but has a similar effect on adverse outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
171
4
20

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 302 publications
(205 citation statements)
references
References 39 publications
10
171
4
20
Order By: Relevance
“…We found that HR was an independent predictor of all-cause, CV, and IHD mortality in these patients. Although this is in keeping with results from other studies, [7][8][9][10][11] we showed that the change in HR achieved during follow-up of hypertensive patients was a better predictor of risk than baseline or final HR. We also showed that, after correction for rate-limiting therapy (␤-blockers and nondihydropyridine calcium channel blockers), HR remained a significant independent risk factor.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We found that HR was an independent predictor of all-cause, CV, and IHD mortality in these patients. Although this is in keeping with results from other studies, [7][8][9][10][11] we showed that the change in HR achieved during follow-up of hypertensive patients was a better predictor of risk than baseline or final HR. We also showed that, after correction for rate-limiting therapy (␤-blockers and nondihydropyridine calcium channel blockers), HR remained a significant independent risk factor.…”
Section: Discussionsupporting
confidence: 92%
“…As in INVEST, 11 there appeared to be a continuous relationship between baseline HR and adverse outcomes with only weak evidence of a noncontinuous relationship for CV mortality. Again, in keeping with INVEST, on-treatment HR was more predictive than baseline HR.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…35 The medical literature on which these recommendations rest is based in large part on the long-term outcome of patients with known CAD or hypertension, suggesting better survival with heart rates in the 60-70 beatsÁmin -1 range but also reporting evidence of adverse survival with lower ranges. [36][37][38][39] These controversies emphasize the problems of applying findings from a patient group in one context, i.e., long-term survival in medical patients, to the more dynamic and shorter term perioperative setting. The association of heart rate control with beta blockade with perioperative outcome remains controversial.…”
mentioning
confidence: 99%
“…Toutefois, cette littérature rapporte également une survie diminuée lorsque la fenêtre a des valeurs plus basses. [36][37][38][39] Toutes ces controverses mettent en exergue les problèmes qui émergent lorsqu'on tente d'appliquer les résultats d'un groupe de patients dans un contexte donné, soit la survie à long terme de patients médicaux, au contexte périopératoire, lequel est à la fois plus dynamique et à plus court terme.…”
unclassified